An Assessment of Physicians’ Recommendations for Colorectal Cancer Screening and International Guidelines Awareness and Adherence: Results From a Thai National Survey - Pausawasdi, Nonthalee; Tongpong, Pongkamon; Geeratragool, Tanawat; Charatcharoenwitthaya, Phunchai (Frontiers in Medicine, 2022)
Background Colorectal cancer (CRC) screening uptake is generally low in the Asia Pacific and physicians’ recommendations affect the screening participation. Objective The study aimed to assess Thai physicians’ recommendations for CRC screening, and the awareness of and adherence to international guidelines. Methods A survey containing questions assessing physicians’ demographic data, screening recommendations, and awareness of the international CRC screening guidelines assessed by clinical vignettes. Independent predictors of physicians’ recommendations for CRC screening were determined by logistic regression analysis. Results Five hundred and eighty-sixth of 1,286 (46%) physicians completed the survey, and 58% of them offered CRC screening. The majority of colorectal surgeons (91%) and gastroenterologists (86%) endorsed screening, whereas 35% of primary care physicians recommended screening. The patient’s age was the only factor influencing the physician’s decision to offer CRC screening (OR, 2.75: 95% CI, 1.61–4.67). Colonoscopy was the most recommended modality among specialists, whereas 60% of primary care physicians offered fecal occult blood tests (FOBTs). The guidelines awareness was noted in 81% of participants, with the highest rates among gastroenterologists and colorectal surgeons. Gastroenterologists were more likely to adhere to the guidelines than surgeons, but both recommended shorter interval surveillance colonoscopy than guidelines recommendations in cases of small hyperplastic rectosigmoid polyps. Conclusions Recommendations for CRC screening and awareness of guidelines vary among different specialties. A low proportion of primary care physicians recommended screening and colorectal surgeons and gastroenterologists recommended shorter intervals for surveillance of small hyperplastic polyp than suggested by guidelines.